MAGMA FLOW IN A CYLINDRICAL CONDUIT: A MATHEMATICAL MODEL - Mikhailova-Filippova M.I.; Fedotov S.A. (My University, 1997)
A mathematical model and a method of calculation are proposed for variable viscosity magma flow in a cylindrical conduit. An example of calculation is given for the conduit radius of 10 m, magma reservoir depth of 30 km, excessive reservoir pressure of 20 bar, magma temperature in the reservoir of 1300°C, and magma viscosity in it of 104, 105 and 106Pa.s. The initial period of the conduit operation is taken to be less than 10 years. The conditions of the conduit freezing (arrested extrusion), the origin of a quasi-stationary regime (steady outflow), and flow with intensive heating of the walls are discussed.